THE LAW OF SHALAT MAKTUBAH FOR SURGICAL PATIENTS IN ACCORDANCE WITH SHAFI’I FIQH REVIEW - Aria Sandra (SYARIAH: Journal of Islamic Law, 2020)
Based on the command of prayer from the verses of al-Qur`an, the Sunnah of the Prophet (peace be upon him) and the opinions of the scholars who are in the circle of Shafi'i schools and also in cross-school, missing the prayer is committing sin except for woman during menstruation. It is remission for them not to pray during menstruation, indeed, it is forbidden. Therefore, Salatmust be performed by every believer. Admittedly, whoever has some accuse due to illness, including someone who has just had surgery and impure with blood as prayer validation. This study examines the law of Maktubah prayers for surgical patient impure with blood as a barrier to prayer validation. The purpose of this study is to find out how the law of prayer is changed for surgical patients and how is the legal solution. The method used in this research is descriptive analysis and data collection through library research. The results of this study concluded that patients undergoing surgery must perform the five daily prayers due to respect for Waqtu. Even if the prayer must be repeated in the future after he recovers from his illness. In this case, the writer advised every Muslim to not looking for excuse to miss prayer.